Otto the cat - Herman, Gail, 1959-; Gorbaty, Norman (New York : Grosset & Dunlap, 1995)
This rebus book is about Otto, a funny cat.
Includes 24 flash cards.
Keywords: Cats -- Fiction; Dogs -- Fiction; Rebuses